Establishment of Embryonic Stem Cell like Cell Colonies from In-vitro Produced Buffalo Compact Morulae - S. Satheshkumar; K. Brindha; M. ShaliniPriya; M. Parthiban; A. Palanisammi; G. Dhinakar Raj (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was aimed at establishing the embryonic stem cells (ESC) like cell colonies from in-vitro produced buffalo (Bubalus bubalis) compact morula (CM). A total of 33 CM were subjected for zonalysis using pronase and embryonic cells were derived by three different methods viz., T 1: Intact CM; T 2: Disaggregation of CM by gentle pipetting and T3: Slicing of CM using Bard Parker blade. The efficiency of establishment of ESC-like cell colonies in the three groups were 66.7, 83.6 and 6.7 per cent respectively. There were no significant differences on the day of attachment and initiation of primary colony formation between T1 and T2 groups. However, the primary colonies established significantly earlier (Day 3.8) in T2 group than in T1 group (Day 4.8). In both the groups, the primary coloniesspread out vigorously exhibiting rapid proliferation rate. The ESC-like cell colonies of T1 and T2 groups survived upto four passages. Immunostaining of CM, primary and passaged ESC-like cell colonies revealed distribution of Oct-4 protein. The study demonstratedsuccessful establishment of ESC-like cell colonies from pipette dissociated blastomeres of in-vitro produced CM.